Shynthesis and Characterizations of Calcium Hydroxyapatite Derived from Crabs Shells (Portunus pelagicus) and Its Potency in Safeguard against to Dental Demineralizations - Raya, Indah; Mayasari, Erna; Yahya, Afdaliah; Syahrul, Muhammad; Latunra, Andi Ilham (International Journal of Biomaterials, 2015)
Crab’s shells of Portunus pelagicus species were used as raw materials for synthesis of hydroxyapatite were used for protection against demineralization of teeth. Calcination was conducted to crab’s shells of Portunus pelagicus at temperature of 1000°C for 5 hours. The results of calcination was reacted with (NH4)2HPO4, then dried at 110°C for 5 hours. Sintering was conducted to results of precipitated dried with temperature variations 400–1000°C for a hour each variation of temperature then characterized by X-ray diffractometer and FTIR in order to obtain the optimum formation temperature of hydroxyapatite is 800°C. The hydroxyapatite is then tested its effectiveness in protection against tooth demineralization using acetate buffer pH 5.0 with 1 M acetic acid concentration with the addition of hydroxyapatite and time variation of immersion. The results showed that the rate of tooth demineralization in acetate buffer decreased significantly with the provision of hydroxyapatite into a solution where the addition of the magnitude of hydroxyapatite is greater decrease in the rate of tooth demineralization.